Tree Species Diversity, Richness, and Similarity in Intact and Degraded Forest in the Tropical Rainforest of the Congo Basin: Case of the Forest of Likouala in the Republic of Congo. (8th August 2016) - Ifo, Suspense Averti; Moutsambote, Jean-Marie; Koubouana, Félix; Yoka, Joseph; Ndzai, Saint Fédriche; Bouetou-Kadilamio, Leslie Nucia Orcellie; Mampouya, Helischa; Jourdain, Charlotte; Bocko, Yannick; Mantota, Alima Brigitte; Mbemba, Mackline; Mouanga-Sokath, Dulsaint; et al.
Abstract : Trees species diversity, richness, and similarity were studied in fifteen plots of the tropical rainforests in the northeast of the Republic of Congo, based on trees inventories conducted on fifteen 0.25 ha plots installed along different types of forests developed on terra firma, seasonally flooded, and on flooded terra. In all of the plots installed, all trees with diameter at breast height, DBH ≥ 5 cm, were measured. The Shannon diversity index, species richness, equitability, and species dominance were computed to see the variation in tree community among plots but also between primary forest and secondary forest. A total of 1611 trees representing 114 species and 35 families were recorded from a total area of 3.75 ha. Euphorbiaceae was the dominant family in the forest with 12 species, followed by Fabaceae-Mimosoideae (10 species) and Phyllanthaceae (6 species) and Guttiferae (6 species). The biodiversity did not vary greatly from plot to plot on the whole of the study area (3.75 ha). The low value of Shannon index was obtained in plot 11 (H ′ = 0.75 ) whereas the highest value was obtained in plot 12 (H ′ = 4.46 ). The values of this index vary from 0.23 to 0.95 in plots P11 and P15, respectively. Results obtained revealed high biodiversity of trees of the forest of Impfondo-Dongou. The information on tree species structure and function can provide baseline information for conservation of the biodiversity of the tropical forest in this area.